YURISDIKSI ICC TERHADAP PENANGKAPAN BENJAMIN NETANYAHU DAN YOAV GALLANT PADA KONFLIK BERSENJATA ANTARA ISRAEL DAN PALESTINA - Hadi, Ahmad Maula; Hazim Khabiri, Muhammad; Nelina Rahayu, Naswa (Ilmu Hukum, Sharia and Law Faculty, Sunan Gunung Djati Islamic State University of Bandung, 2024)
Abstract The aim of this research is to analyze and discover war crimes and humanity that occurred in the armed conflict between Israel and Palestine, as well as analyze and discover the jurisdiction of the International Criminal Court which has issued arrest warrants for Benjamin Netanyahu and Yoav Gallant in this armed conflict. The method used in this research is a qualitative method with a normative juridical approach which examines research issues using various international legal instruments and doctrines from experts. The results of the analysis state that the war and humanitarian crimes that occurred in the Israeli and Palestinian conflict did not use and pay attention to restrictive legal instruments in international law, human rights principles, the ius cogen principle, and the Martens clause principle which prioritize the interests of peace, and prevent so that the conflict does not escalate further. The ICC as one of the institutions that has the authority to take action against perpetrators of international crimes has the opportunity to optimize its steps in making arrest warrants based on the 1998 Rome Statute, although it was found that the political element is still very strong considering that UN Security Council Resolutions are often